2018
DOI: 10.1016/j.reseneeco.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Feldstein meets George: Land rent taxation and socially optimal allocation in economies with environmental externality

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Further, in Section 5, we analyzed the effects of three kinds of taxes and showed that the growth rate will increase even if the tax revenue is wasted. Particularly, these outcomes indicate that the government could use the tax revenue to finance other useful expenditures, such as environmental protection (Dao and Edenhofer 2018;, reduction in income and wealth inequality (Koethenbuerger and Poutvaara 2009;Schwerhoff et al 2020) or public infrastructure (Bosi and Pham 2016). Additionally, in our model, the whole tax incidence falls to the landowners because the marginal productivity of capital remains constant.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Further, in Section 5, we analyzed the effects of three kinds of taxes and showed that the growth rate will increase even if the tax revenue is wasted. Particularly, these outcomes indicate that the government could use the tax revenue to finance other useful expenditures, such as environmental protection (Dao and Edenhofer 2018;, reduction in income and wealth inequality (Koethenbuerger and Poutvaara 2009;Schwerhoff et al 2020) or public infrastructure (Bosi and Pham 2016). Additionally, in our model, the whole tax incidence falls to the landowners because the marginal productivity of capital remains constant.…”
Section: Discussionmentioning
confidence: 87%
“…In what follows, we analyze if the main insights and results gained by others (c.f. Tirole 1985;Homburg 1991;Fane 1984;Chamley and Wright 1987;Grossman and Yanagawa 1993;Hashimoto and Sakuragawa 1998;Stauvermann 2002;Koethenbuerger and Poutvaara 2009;Edenhofer et al 2015;Dao and Edenhofer 2018) can be confirmed. The novelty of the paper is that it is the first study to consider, in an overlapping generations (OLG) framework, the possibility of using land for production purposes or housing purposes and the subsequent effect of different land taxes and the redistribution of the respective tax revenue to the young generation on economic growth.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…As is standard in the literature [ 54 , 55 , 56 , 57 , 58 , 59 ], the pollution emissions per labor unit in period t + 1 (noted as ) are determined by the function below: …”
Section: Model Set Upmentioning
confidence: 99%
“…In Islam, leasing is called ijarah which has the meaning of services, rewards, rent, or wages [1]. Ijarah is one way to earn income by exchanging services owned or renting goods for a certain period to meet the needs of daily life [2].…”
Section: Introductionmentioning
confidence: 99%